Price promotions based strategy : is brand equity created? - Pinheiro, Duarte de Lemos (2013)
The food distribution market has been characterized by strong and fierce price competition. Players in this market constantly make use of price appeal to attract customers and increase sales. Two main techniques have emerged over the recent years: EDLP and Hi-lo promotions. The first consists of keeping prices lower than competitors based on an efficient cost structure. The latter consists of having particular products on promotion for a certain period of time. As consumers are being bombarded with price related messages, their price sensitivity and also deal sensitivity has been increasing. This paper revolves around the particular case of Pingo Doce – one of the largest players in the Portuguese food distribution market. In 2012 after several years of practicing an EDLP pricing strategy, the company swapped to a Hi-lo pricing strategy on a remarkable and memorable day. This move basically matched what all competitors were already doing, despite the fact that the company had strengthened its position among consumers through a different pricing strategy in the years before. The research aimed to understand if the turnaround produced positive effects in what concerns brand equity creation or likelihood of brand equity creation in the long run given a medium term perspective and taking into consideration consumers’ perceptions only. It was concluded that for some factors it worked well and for some others there were significant doubts. Namely, the change in price positioning allowed Pingo Doce to strengthen its brand in what concerns: awareness – as consumers were proven to be generally aware of its promotions; value of the differentiating factor associated to Pingo Doce promotions driven by its “immediate discount” factor ; increased perceptions on a socially effortful personality trait during a period of economic recession; perceived benefit of its promotions monetary/savings which increases deal value; and finally, improvements on Pingo Doce price perceptions due to the appearance of promotions. On the other hand, the strategy could not be proven efficient in what concerns: attracting new customers who would be promotion driven (mainly from Continente as it was the company goal); existence of perceptions of hedonic benefits that would help to increase deal value and promotions evaluation; price perceptions of Continente regular customers were still quite low when compared to the rest of the sample.